Synthesis of a crystalline zeolitic imidazole framework-8 nano-coating on single environment-sensitive viral particles for enhanced immune responses. Issue 5 (15th February 2023) - Wang, Liuyang; Lin, Xuan; Sheng, Yanan; Zhu, Hongyu; Li, Zhengjun; Su, Zhiguo; Yu, Rong; Zhang, Songping
Abstract : Unstable foot-and-mouth disease virus particles were armored with nano-sized crystalline ZIF-8 by an elaborately manipulated biomineralization reaction and showed improved immune responses. Abstract : Encapsulating antigens with zeolitic imidazole framework-8 (ZIF-8) exhibits many advantages in vaccine development. However, most viral antigens with complex particulate structures are sensitive to pH or ionic strength, which cannot tolerate harsh synthesis conditions of ZIF-8. Balancing the viral integrity and the growth of ZIF-8 crystals is crucial for the successful encapsulation of these environment-sensitive antigens in ZIF-8. Here, we explored the synthesis of ZIF-8 on inactivated foot and mouth disease virus (known as 146S), which is easily disassociated into no immunogenic subunits under the existing ZIF-8 synthesis conditions. Our results showed that intact 146S could be encapsulated into ZIF-8 with high embedding efficiency by lowering the pH of the 2-MIM solution to 9.0. The size and morphology of 146S@ZIF-8 could be further optimized by increasing the amount of Zn 2+ or adding cetyltrimethylammonium bromide (CTAB). 146S@ZIF-8 with a uniform diameter of about 49 nm could be synthesized by adding 0.01% CTAB, which was speculated to be composed of single 146S armored with nanometer-scale ZIF-8 crystal networks. Plenty of histidine on the 146S surface forms a unique His-Zn-MIM coordination in the near vicinity of 146S particles, which greatly increases the thermostability of 146S by about 5 °C, and the nano-scale ZIF-8 crystal coating exhibited extraordinary stability to resist EDTE-treatment. More importantly, the well-controlled size and morphology enabled 146S@ZIF-8(0.01% CTAB) to facilitate antigen uptake. The immunization of 146S@ZIF-8(4×Zn 2+ ) or 146S@ZIF-8(0.01% CTAB) significantly enhanced the specific antibody titers and promoted the differentiation of memory T cells without adding another immunopotentiator. This study reported for the first time the strategy of the synthesis of crystalline ZIF-8 on an environment-sensitive antigen and demonstrated that the nano-size and appropriate morphology of ZIF-8 are crucial to exert adjuvant effects, thus expanding the application of MOFs in vaccine delivery.